Optimalisasi Literasi Komunikasi Parenting melalui Media Digital dalam Penguatan Pola Asuh Positif (Lembaga Pengembangan Kinerja Dosen, 2026)
Parenting communication literacy is a fundamental competence that influences children’s growth in cognitive, emotional, and social domains. Initial findings at Posyandu Teratai, South Tangerang, revealed that many mothers still relied on authoritarian and less dialogical communication, which limited children’s confidence and engagement. In response, the Community Service (PKM) team of Universitas Pamulang implemented a program entitled Optimizing Parenting Communication Literacy through Digital Media. The activities were designed using participatory strategies such as lectures, interactive group discussions, simulation exercises, and the dissemination of digital learning materials in the form of modules and videos. The program outcomes demonstrated considerable improvement in mothers’ knowledge and attitudes toward positive communication practices, including the ability to listen actively, provide encouragement, and employ digital platforms as continuous learning resources. Furthermore, the integration of digital tools enabled mothers to access and exchange information beyond formal training sessions. The broader impact of the program was the establishment of a collaborative learning community at Posyandu, which not only supported families in applying positive parenting approaches but also reinforced community-level awareness of effective communication in child-rearing.